2018
DOI: 10.1080/03007995.2018.1495621
|View full text |Cite
|
Sign up to set email alerts
|

Risk of chemotherapy-induced febrile neutropenia with same-day versus next-day pegfilgrastim prophylaxis among patients aged ≥65 years: a retrospective evaluation using Medicare claims

Abstract: Among Medicare patients receiving chemotherapy and PP in US clinical practice, PP was administered before the recommended timing in 5% of cycles and FN incidence was significantly higher in these cycles. Along with prior research, study findings support recently updated US practice guidelines indicating that PP should be administered the day after chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
3
13
0
Order By: Relevance
“…The risk of FN was higher in all cycles for patients receiving same-day pegfilgrastim, odds ratio (OR), 1.5 (95% CI 1.3-1.6). Similar findings were reported in follow-up studies using private healthcare claims data spanning 2010-2015 (OR ¼ 1.3, 95% CI 1.2-1.4) and using Medicare claims data (OR ¼ 1.3, 95% CI 1.2-1.4) 64,65 . A recent systematic review of the literature on this topic concluded that the literature supports "administration of pegfilgrastim to patients at least 1 d after the completion of a chemotherapy cycle" 66 .…”
Section: The 2010ssupporting
confidence: 83%
“…The risk of FN was higher in all cycles for patients receiving same-day pegfilgrastim, odds ratio (OR), 1.5 (95% CI 1.3-1.6). Similar findings were reported in follow-up studies using private healthcare claims data spanning 2010-2015 (OR ¼ 1.3, 95% CI 1.2-1.4) and using Medicare claims data (OR ¼ 1.3, 95% CI 1.2-1.4) 64,65 . A recent systematic review of the literature on this topic concluded that the literature supports "administration of pegfilgrastim to patients at least 1 d after the completion of a chemotherapy cycle" 66 .…”
Section: The 2010ssupporting
confidence: 83%
“…8 Additional studies on this topic are retrospective, single center designs and retrospective cohort studies based on insurance claims data. [9][10][11][12][13][14][15] Several of these studies are older and were published prior to the approval of the autoinjector device.…”
Section: Literature Evaluationmentioning
confidence: 99%
“…Weycker and colleagues published a series of retrospective cohort studies examining patterns of febrile neutropenia related to CSF administration. 14 , 15 These studies included patients with non-metastatic breast cancer and NHL, as well as non-metastatic ovarian and lung cancer in 1 study. A statistically higher incidence of febrile neutropenia with same day administration (day 0) compared to administration on days 1 to 3 during cycle 1 (based on Medicare claims: 11.4% vs. 8.4%, respectively; OR, 1.4; 95% CI, 1.3 to 1.6; p < 0.001; based on private insurance claims: 3.4% vs. 2.5%; OR, 1.4; 95% CI, 1.2 to 1.7; p < 0.001).…”
Section: Summary Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Granulocyte colony‐stimulating factors (G‐CSFs) are growth factors that can stimulate the bone marrow to produce neutrophils and minimize the risk of developing FN in these patients. Pegylated recombinant human granulocyte‐colony stimulating factor (PEG‐rhG‐CSF) is currently the most commonly used prophylactic G‐CSF agent in clinical practice 1–3 . Improved patient compliance with chemotherapy treatment further favors its use clinically 4 …”
Section: Introductionmentioning
confidence: 99%